Survival outcomes in severe congenital versus non-congenital pulmonary hypertension. Issue 1 (19th January 2016) - Arnott, Clare; Boehm, Christiane; Lau, Edmund; Celermajer, David S
Abstract : Objective: Since 2006, our institution has cared for 70 patients with pulmonary arterial hypertension (PAH) and severe right ventricular (RV) hypertension; 44 with congenital heart disease (CHD) had Eisenmenger syndrome (ES) and 26 had PAH without CHD. We sought to determine and compare 'real-world' survival outcomes and cause of death in these two distinct groups. Methods: An observational study of consecutive adult patients from our CHD or PAH clinics with RV systolic pressure ≥80 mm Hg (on echocardiography or right-heart catheter). Detailed patient demographics, investigations and outcomes at baseline and follow-up were reviewed. Results: Patients with ES were younger than non-CHD group (39±9 vs 64±14 years, p<0.001) with a lower proportion of women (61% vs 85%; p=0.04), and higher RV systolic pressure. Estimated 1-year, 3-year and 7-year survival were not significantly different between the groups (98%, 95% and 74% ES; 100%, 92% and 63% non-CHD, p=0.52). In patients with non-CHD, poorer survival was associated with a diagnosis of connective tissue disease (HR 6.90, 95% CI 1.21 to 39.3) and number of PAH therapies (HR 2.8, 95% CI 1.03 to 7.59). Mortality was directly attributed to PAH in 75% of non-CHD group compared with 31% in patients with ES (p=0.049), many of whom died from infection or bleeding. Conclusions: We report favourable 7-year survival in adults with PAH and systemic RV pressures—equivalent in ES and non-CHD groups. Those with non-CHD predominately died of cardiac complications of PAH, as distinct from those with ES, many of whom died from complications of chronic cyanosis.